How coronavirus disease 2019 entered Africa and the Middle East: a case study from Egypt. (12th August 2020) - Khattab, Nourhan M; Vermund, Sten H; Hu, Yifei
Abstract: Background: We report the first person with SARS-CoV-2 in Egypt. Methods: We interviewed the index case and contacts. Results: The 36-year old man was healthy when he traveled on business to Wuhan, China in January 2020. Upon his return to Cairo, he became ill, went to work, and subsequent autochthonous viral spread occurred. Conclusion: We linked SARS-CoV-2 importation to global business travel. The extent to which physical distancing, hand/face/surface hygiene, mask use, viral testing/contact tracing, restricted travel, small gatherings, and/or stay-in-residence mandates will be implemented and limit further spread in the Middle East and North Africa remains to be seen.